On the provenience and meaning of the concept “exponent” in Kant’s Critique of pure reason - Rodrigues Ferreira Perez, André (Con-Textos Kantianos. International Journal of Philosophy, 2021)
In this text I shall explore the meaning of the concept “exponent” in the first Critique by resorting to its provenience. Beginning with a brief analysis of the two meanings Kant ascribes to it the Critique, the exponent of a series and the exponent of a rule, I intend to point out that by means of Kant’s concept of analogy, intimately linked with proportion, we can find a route into some of the mathematics textbooks of the 18th century, which shed great light in the matter. Thereafter, as a transition for returning to the Critique, we shall see how, in the Duisburgscher Nachlass, the exponent plays a central role for Kant as he thinks the emergency and necessity of rules in Philosophy, in comparison to Mathematics. In this way I hope to show how the “exponent” is taken up by Kant and made fruitful, especially for the Analogies of experience.